STUDENTS’ ABILITY IN ANSWERING HIGHER ORDER THINKING SKILLS TEST ON ENGLISH SUBJECT - Jalmi Harti; Febria Sri Artika; Irwandi Irwandi (ELP (Journal of English Language Pedagogy), 2019)
Higher Order Thinking Skill is the complex of thinking process in transfer information, critical thinking, creative thinking; problem solving and making decision that involve student’s realistic reasoning. The background of the problem are students were lack of transfer information of their background knowledge and the students were still lack of expressing their idea. This research used descriptive quantitative research. The data analysed by using document analysis method proposed by Sugiyono. The researcher used the first semester final test, multiple choice analyse Higher Order Thinking Skills (HOTS) question and students test result to collect the data. The population of this research was 139 third grade students of SMAN 1 Bukittinggi. This research used cluster random sampling technique. The researcher took 20% respondents there were 28 students as informants. The researcher analysed students’ test result of seven samples in each class. The results of the study generally indicate that the teacher has applied some Higher Order Thinking Skills test in english subject. The total of Higher Order Thinking Skills (HOTS) question was 15% and students’ test result of Higher Order Thinking Skills (HOTS) was 58.2%. From these data, it can be concluded that ability of students to answer Higher Order Thinking Skills (HOTS) questions was low.